GC/MS Analysis and Protective Effects of Mentha longifolia L. Essential Oil Against Antituberculosis Drug-Induced Organs Toxicity in Wistar Albino Rats - Usama K. Abdel-Hameed; Abdulaziz S. Abualghaith; Shaza H. Aly; Mohamed Mostafa Soliman; Lamiaa Adnan Munshi; Safia A. A. Mohammed; Omayma A. Eldahshan; Eman A. R. Abdelghffar (Plants)
Mentha longifolia (L.) L., also known as wild mint, is a perennial herbaceous plant that belongs to the Lamiaceae family. This study aimed to investigate the effects of essential oil of M. longifolia (MLEO) on oxidative stress and inflammatory responses in the liver and kidneys in the context of drug-induced liver injury caused by the anti-TB drugs rifampicin, isoniazid, and pyrazinamide (INH-RIF-PZA). The chemical composition of MLEO was characterized using GC/MS analysis, which revealed the presence of pulegone, trans-p-menthan-3-one, piperitenone, and β-caryophyllene as its major volatile constituents. An INH/RIF/PZA mixture was administered to Wistar rats for 30 days, and silymarin was administered as a standard drug. MLEO was administered p.o. at doses of 50 mg and 100 mg/kg b.w. Both doses of the MLEO therapy effectively regulated all biochemical indicators of hepatic impairment and reduced the damage caused by the INH/RIF/PZA mixture. It may be deduced that MLEO has the ability to protect organs against INH/RIF/PZA-induced damage and could potentially be a valuable natural remedy for treating anti-TB-induced liver and kidney injuries.